THE COMPLIMENT RESPONSES USED BY MAKASSARESE NATIVE SPEAKER - Natsir, Nurasia (JOURNAL OF ADVANCED ENGLISH STUDIES, 2020)
Compliment responses are one of speech act types in pragmatic study. This study is aimed (1) to investigate the strategies used by the American and Makassarese people in responding to the complim ent, (2) to compare the response tendencies used by American and the Makassarese people based on Gender and age; and (3) to investigate the cultural influences on the American and Makassarese response.The research was a comparative study which and used a descriptive- qualitative approach. The data were collected from youtube.com and DCT questionnaire. The data were analyzed using a number of techniques, namely noting down the utterances, categorizing the responses identified based on Holmes’ semantic formula and explaining the cultural influences based on their responses. Firstly, the research result revealed that both the American and Makassarese people used 3 compliment strategies: accepting, evading and refusing. Americans would use the evading strategy when the speaker and his interlocutor were good friends; while a Makassarese would either use the evading strategy or the refusing strategy in his responses, when the speaker and his interlocutor were of a different kinship hierarchy, such as between the older and the younger brothers or sisters and between husband and wife. Secondly, The comparison of the compliment responses between the American and Makassarese males indicated that an American male had the tendency to evade a compliment in every topic except teenager had tendency to accept the compliment in any topic. While a Makassarese male tend to receive the compliment for all the topics, except for the comp liment for an achievement.on the other hand, an American woman had tendency to accept a compliment for all topics, but an older woman had a tendency to refuse a compliment. a Makassarese woman, had also a tendency to accept a compliment for all topics. Finally, Makassarese people, both men and women had the tendency to accept, evade or refuse compliments when they had kinship.